Pemetaan Kompetensi Dasar Mata Pelajaran Matematika Siswa SMA Di Kabupaten Bengkalis - Susda Heleni (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2012)
The low quality of education in Indonesia, has been widely recognized by variousparties, especially by education observers. Based on the necessary effort to improve the quality ofeducation, one to carry out the study based on analysis of problems in the field. This study aims toobtain a clear picture of (a) to identify the competency standard / basic competencies that have notmastered high school students in Bengkalis discussion on any subject Maths subjects tested on the UN,(b) identify the factors that cause students not master the competency standard / basic competencies, (c)design and develop a model for solving the problem. Study sample was held at SMAN SMAN 1Bengkalis and High Cliff. The focus of research is the management system, teachers, educationalfacilities, which refers to the national standards of education and culture. Data were collected throughclassroom observations, interviews, questionnaires, and documentation. This research resulted inalternative solutions to problems (1) Training for teachers of mathematics-based subjects MGMP. (2)Guidance and stabilization of materials for teachers of educational background do not fit. (3) Trainingfor school management and administrative staff. All activities ready to be implemented in concreteterms through community service activities through cooperation with the Department of HigherEducation D2PM Bengkalis.